Impact of Task Variation and Job Knowledge on Employee Performance Through Value of Service - Prasetyawan, Agung; Junaidi, Achmad; Irawati, Marsha Ayunita; Subekti, Heny (Universitas Negeri Semarang, 2024)
This research aims to analyze the influence between task variation and knowledge of the job on employee performance using the value of services as the moderating variable. This research tries to fill the inconsistency of previous research findings and fill the existing literature gap. This research uses 133 active employees from Pemerintah Kota Semarang, that are collected by purposive sampling method. This research is quantitative research using Structural Equation Modelling (SEM). The result shows that task variation has a significant and positive influence on the value of service, but is not significant on employee performance. Furthermore, knowledge of a job has a positive and significant influence on the value of services and employee performance. This research also concludes that the value of service has a positive and significant mediate influence on employee performance.